2023
DOI: 10.1002/cey2.339
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent interactions on the electrocatalytic oxidation of ethanol on a Pt/C electrocatalyst

Abstract: Due to their environmentally friendly nature and high energy density, direct ethanol fuel cells have attracted extensive research attention in recent decades. However, the actual Faraday efficiency of the ethanol oxidation reaction (EOR) is much lower than its theoretical value and the reaction kinetics of the EOR is sluggish due to insufficient active sites on the electrocatalyst surface. Pt/C is recognized as one of the most promising electrocatalysts for the EOR. Thus, the microscopic interfacial reaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…11 Therefore, enormous efforts have been made to develop more thermodynamically favorable organic oxidation reactions for replacing the OER. [12][13][14] In recent years, a wide range of organic oxidation reactions, including the oxidation of alcohols, 15 ammonia, 16 urea, 17 hydrazine 18 and biomass-derived compounds 19,20 have been explored to establish hybrid electrochemical water splitting. Particularly, the study on electrocatalytic oxidation of biomass derivatives has attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, enormous efforts have been made to develop more thermodynamically favorable organic oxidation reactions for replacing the OER. [12][13][14] In recent years, a wide range of organic oxidation reactions, including the oxidation of alcohols, 15 ammonia, 16 urea, 17 hydrazine 18 and biomass-derived compounds 19,20 have been explored to establish hybrid electrochemical water splitting. Particularly, the study on electrocatalytic oxidation of biomass derivatives has attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…The Electrochemical Ethanol Oxidation Reaction (EOR) constitutes the anodic reaction for a myriad of renewable energy conversion devices, [1] including Direct Ethanol Fuel Cells (DEFCs), [2] hybrid ethanol electrolysis, [3] and zinc‐ethanol‐air batteries [4] . Throughout the EOR process, ethanol initially adsorbs onto the catalyst surface, evolving into several adsorbed intermediates before final desorption [5,6] . To date, over 40 possible intermediates have been identified, [7] suggesting varied reaction pathways and correspondingly diverse catalytic performances across different catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Throughout the EOR process, ethanol initially adsorbs onto the catalyst surface, evolving into several adsorbed intermediates before final desorption. [5,6] To date, over 40 possible intermediates have been identified, [7] suggesting varied reaction pathways and correspondingly diverse catalytic performances across different catalysts. Therefore, the accurate detection of reaction intermediates is crucial for elucidating the reaction mechanism, thereby improving selectivity and reducing the reaction barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Metal cations in the electrolytes have significant effects on reaction pathways of CO 2 reduction, oxygen reduction reaction, and hydrogen evolution reaction in addition to the role in conducting ions. For example, metal cations facilitated the C–C bond formation in the CO 2 reduction on Cu electrodes . The cation and anion effects on the electrooxidation of ethanol were observed in alkaline and acidic electrolytes, respectively, while the alkali metal (AM) cation effect in an acidic electrolyte has not been well investigated yet.…”
mentioning
confidence: 99%
“…For the methanol oxidation, the catalytic performance correlated monotonically to the the hydration energy of the alkali metals, which affected the water activation through formation of OH ad –M + (H 2 O) x clusters at the interface . The theory has been used to explain the cation effect in other electrooxidation systems in the alkaline media. ,, However, few studies of the cation effect were reported in acidic media because of the complex interaction among cations, anions, and hydrated water molecules. Here, it is found that the cations affected the formation of AM + sulfate ion pairs evidenced by the in situ Raman spectroscopy.…”
mentioning
confidence: 99%